MENINGKATKAN HASIL BELAJAR AKUNTANSI PERUSAHAAN DAGANG MENGGUNAKAN MODEL PEMBELAJARAAN KUMON - Rijal, Qori Aditya, (JURNAL PENDIDIKAN IPS, 2023)
This research is motivated by the low value of accounting subjects in trading company material, this is indicated by the low learning outcomes, which only reach 55 while what must be achieved is 75 according to the KKM that has been set by the school. Likewise, the way teachers carry out learning is still conventional without using less effective learning methods. This research focuses on the use of the Kumon learning method in accounting learning on trading company material, based on these problems, the objectives to be achieved are (1) to determine the increase in the learning activities of class X students of SMK Negeri 1 Patumbak through the application of the Kumon learning model (2) to determine improvement of accounting learning outcomes for students of class X Smk Negeri 1 Patumbak through the application of the Kumon learning model. The method used in this research is classroom action research (CAR) using the KUMON learning model. Taggart which consists of two cycles. Data was collected through observation and field notes. The subjects of this study were students of class X AK 1 at SMK Negeri 1 Patumbak. Medan city, which consists of 32 people consisting of 22 women and 10 men. The results of the study using the Kumon learning model in accounting learning material for trading companies showed an increase in activity in the learning process. Students look very active and very happy to participate in learning activities, this is shown by the enthusiasm of students who are very high. Similarly, the acquisition of student learning outcomes the average value in the first cycle which reached 60% with a percentage of 74.3%, the second cycle the average value of the students reached 90%. Based on the results of the study, it can be concluded that learning using the Kumon learning model can improve student learning outcomes. From the results of this study, there are several suggestions for principals, teachers, and other researchers to be able to develop and continue the research that has been done so as to obtain maximum results.